The Effect of Psychological Well-Being on Employee Performance through Work Engagement as an Intervening Variable in Employees of PT X - Aulia Dwi Safitri; Muhammad Husain (Universitas Negeri Surabaya, 2026)
PT X, established in 2021, is a culinary company in the food.and beverage industry. This study aims to examine the effect of psychological well-being on employee performance using work engagement as mediating variable in employees of PT X. A quantitative approach was used in this study with a saturated sampling technique involving 83 initial respondents; 79 respondents were analysed, while 4 respondents were excluded because they did not participate in completing the questionnaire. Structural Equation Modelling was used for data analysis with assistance of SmartPLS 3.2.9 software to obtain objective results in testing the influence between variables. The results of data processing and hypothesis testing provided empirical evidence that psychological well-being has a positive and significant effect on employee performance, psychological well-being has a positive and significant effect on work engagement, work engagement has a positive and significant effect on employee performance, and work engagement significantly mediates the effect of psychological well-being on employee performance. This implies that companies need to improve the psychological well-being of employees by encouraging work engagement, which will have a positive impact on improving employee performance.